Melampaui Oposisi Biner: Dekonstruksi Sebagai Strategi Pembacaan Tanda Dalam Semiotika Struktural - Aman Sobirina; Aminullah; Abdul Matin Bin Salmand (Yayasan Azhar Amanaa Yogyakarta, 2026)
This article examines deconstruction as a critical reading strategy against the binary opposition system embedded in structural semiotics. Ferdinand de Saussure's structural semiotics built its foundation upon binary opposition principles such as signifier, langue, and synchrony, which are considered stable and hierarchical. However, Jacques Derrida through the concept of différance fundamentally challenges this stability by arguing that meaning is never fully present but always deferred and differentiated through an endless chain of signifiers. This study employs a qualitative library research method by analyzing primary texts from Derrida and Saussure alongside secondary sources from relevant philosophical and linguistic literature. The results demonstrate that deconstruction does not destroy the semiotic system but rather opens a space of free play of meaning that structural semiotics attempted to close. Différance as a reading strategy reveals that every sign always carries a trace of what it excludes, so that binary opposition is never truly stable. This study contributes to a deeper understanding of poststructuralist philosophy of language and offers a critical perspective for reading texts beyond rigid structural boundaries.